Komodifikasi Aksara Bali Sebagai Usaha Ekonomi Kreatif di Kabupaten Gianyar - I Wayan Anggara; I Gusti Ngurah Sudiana; I Wayan Wastawa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
The purpose of research is the research aimed to seek, describe and analized Commodification of Balinese letter as a Creative Economic movement in Gianyar Regency. This research is using the commodification theory, symbolize theory, and the social impact theory. The kind of research is the qualitative form, by using the primarily data which derived from the result of the observation, interview, and also documentation, while the secondary data, there were gained from the printed materials, impirical research, and also relevant references that were implied in the research’s tittle. The method of research is The research was using purposive sampling technique. The data collection was gained by using the observation technique, interview, references studies, and documentation study. After the researcher gained the data, it would be analyzed by reduction, classification, and conclusion. The result and conclusion of research can be explained through several matters, there would be: (1) The form of Aksara Bali or Balinese Letter commodification in the form of creative economy industry in Gianyar are in nametag, inscriptions, printed media, and name board. (2) The form of Aksara Bali or Balinese letters product of creative economy industry is by written with the line up term in the economical product, with the Swalalita form of letters which included in the group of warga Aksara Bali or common Balinese letters, completed with the pasang pageh Aksara Bali or the rules in Balinese letters, by following the Harswa and Dirgha term of rules. (3) The impact of Aksara Bali or Balinese letters being existed in the creative economy industry in Gianyar is the socioreligious of the Gianyar Community identity is getting bolder with the both culture and Hindus religion, yet impacted the gradually of the degradation of the sacredness of the appliance of the Aksara Bali or Balinese letters itself, but economically, it enhanched the artists’ income but affected the lost of magical value and turned to become profanity of the Aksara Bali or Balinese letters in Gianyar Regency.